The Distributional Effects of Oil Price Changes on Household Income: Evidence from Mali - Kpodar, Kangni (2012)
Many net oil-importing developing countries, particularly African economies, have faced economic difficulties with high oil price increases. As a case study, this paper assesses the distributional effects of a rise in various petroleum product prices in Mali using a standard computable general equilibrium model. The results suggest that rising diesel prices primarily affect richer households, while the poorest ones tend to suffer more from higher kerosene and gasoline prices. Overall, the impact of fuel prices on household budgets shows a U-shaped relationship with expenditure per capita. Regardless of the oil product considered, high-income households benefit disproportionately from oil price subsidies. This suggests that petroleum price subsidies are ineffective in protecting the income of poor households compared with a targeted subsidy.